2021
DOI: 10.1177/23094990211051492
|View full text |Cite
|
Sign up to set email alerts
|

Intra-medullary antibiotics perfusion (iMAP) for the control of fracture-related infection early after osteosynthesis

Abstract: Purpose In our hospital, cases of bone and soft tissue infections have been treated with continuous local antibiotics perfusion that allows for continuous circulation of antibiotics throughout the infected lesion. We termed this treatment “intramedullary antibiotics perfusion (iMAP)” for bone infection such as fracture-related infection (FRI) and “intrasoft tissue antibiotics perfusion” for soft tissue infection. Many cases are treated with both modalities. To introduce iMAP, this study focused on the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In addition, the synergistic effect of GM with other antimicrobial agents on staphylococcal biofilms has been reported previously (Dall et al, 2018). GM has a long history of local administration in the form of antibiotic-loaded cements (Vugt et al, 2019), and is also used for systemic administration by intramedullary antibiotic perfusion (Maruo et al, 2021). GM seemed a good candidate for local antibiotic treatment.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the synergistic effect of GM with other antimicrobial agents on staphylococcal biofilms has been reported previously (Dall et al, 2018). GM has a long history of local administration in the form of antibiotic-loaded cements (Vugt et al, 2019), and is also used for systemic administration by intramedullary antibiotic perfusion (Maruo et al, 2021). GM seemed a good candidate for local antibiotic treatment.…”
Section: Discussionmentioning
confidence: 84%
“…We present a case series of CLAP therapy, a novel drug delivery system that ensures consistent concentrated local antibiotic administration. CLAP therapy, originally proposed by Maruo in 2020, has recently been recognized as a treatment option for bone and soft tissue infections in Japan [ 7 , 8 ]. Himeno et al reported about the successful treatment of patients with severe infections of the lower limb, including abscesses and osteomyelitis, using CLAP [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we employed a novel local antibiotic therapy at our institution to manage acute deep infections after open fractures. We report a series of cases to demonstrate the efficacy and safety of our novel continuous local antibiotic perfusion (CLAP) therapy [ 7 , 8 ] applied to acute deep infections after open fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the concept of CLAP, we had previously devised iMAP. [10] Initially, we treated FRIs with iMAP combined with a simple drainage tube; however, in many cases, the tube was often occluded, leading to an increase in the serum concentration of gentamicin. Thereafter, we combined iMAP with a suction system, which also delivered antibiotics to the surrounding soft tissue, to create a comprehensive antibiotic perfusion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In iMAP, a daily dose of antibiotics was diluted with a small amount of saline and continuously infused at a low rate using a bone marrow needle placed near the infected site, allowing the delivery of a su cient local concentration of the agent. [10] In iSAP, doublelumen tubes for injection and drainage are placed in the soft tissue surrounding the focus of infection; the antibiotic is administered at the same dose as iMAP via one of the tubes, and constant negative pressure is applied by the other tube to create a perfusion route for the antibiotic. In combination with iMAP and iSAP, the antibiotic in ltrates both the affected bone and surrounding soft tissue due to the assistance of negative pressure.…”
Section: Introductionmentioning
confidence: 99%